Evaluation of competency-based syllabi of the nursing curriculum at a public university, Perú - Herrera García, Yamira Iraisa (2023)
Objetive: This research was carried out with the objective of evaluating in two moments the structural elements of the syllable with a competency approach and the articulation with the graduation profile of the Nursing study program of the National University Toribio Rodríguez de Mendoza de Amazonas, 2021. Method: The methodology used was a quantitative approach, documentary review technique, observational, comparative and cross-sectional design. The sample was represented by 42 syllables. The instrument was a checklist, with adequate validity (VC=4.7>de VT=1.64). For data processing, the statistical package IBM SPSS v.25 was used and for the analysis, the non-parametric statistical test of WILCOXON with 95% confidence and 0.05 margin of error. Main results: The results were that; At first, 69.00% of the syllables did not meet the requirements for review of the elements: general information, summary, generic competencies, course competencies, evaluation criteria, content programming, learning indicators and evaluation, teaching-learning strategies, assistance and disqualification, educational resources, evaluation and communication of results, evaluation instruments and bibliographic references and 31.00% of the syllables evidenced the elements; however, in the second moment, 95.20% of the syllables met the estimated and described requirements for the review. Overall conclusion: Concluding that the second moment of the evaluation of the syllables differs significantly from the first, due to the systematized pedagogical accompaniment of the multidisciplinary team in the nursing academic training.